Case Report: SAPHO Syndrome Mimicking Bone Metastases During Treatment With Pembrolizumab for Non-small Cell Lung Cancer - Kubo, Yuko; Ito, Kimiteru; Fujiwara, Yutaka; Yoshida, Tatsuya; Kusumoto, Masahiko (Frontiers in Medicine, 2021)
A 69-year-old female with recurrent stage IV squamous cell lung carcinoma and metastatic abdominal lymph node but not bone metastases was being treated with pembrolizumab. Four months after starting the recurrent treatment, the tumour reduced in size but she began to complain of back pain and palmar rash. A bone scan showed uptake lesions in the left sternocostal joints and vertebrae, while spine magnetic resonance imaging (MRI) showed multiple lesions in the thoracic vertebrae. Her heterogeneous lesions, such as skin and multiple bone manifestations, were comprehensively diagnosed as SAPHO syndrome by different experts. Furthermore, the SAPHO syndrome was suspected to be an immune-related adverse event induced by pembrolizumab, and pembrolizumab withdrawal and prednisolone treatment were performed. Subsequently, her symptoms improved and the follow-up imaging findings showed that the bone lesions had almost disappeared. This case demonstrates that SAPHO syndrome mimicking bone metastases developed during treatment with pembrolizumab. SAPHO syndrome is rare and bone lesions related to the disease may be misdiagnosed as bone metastases. Therefore, it is important in the future for various physicians to have a better understanding of SAPHO syndrome and to consider the potential relationship between this disease and immunotherapy.